The DUBR/miR-210-5p/RETSAT Axis in Cholesterol-Associated Steatohepatitis: Clinical Signatures and Molecular Mechanisms - Mahmoud Abdelzaher, Hana (AUC Knowledge Fountain, 2025)
Metabolic-associated fatty liver disease (MAFLD) represents an increasing global health challenge, with cholesterol-associated steatohepatitis (CASH) emerging as a distinct pathological entity warranting investigation. While CASH demonstrates unique features compared to traditional triglyceride-driven steatohepatitis, its underlying molecular mechanisms remain poorly understood. This study investigates a novel regulatory axis involving DPPA2 Upstream Binding RNA (DUBR), miR-210-5p, and retinol saturase (RETSAT). 170 patient samples revealed progressive axis dysregulation in disease states, with RETSAT emerging as a highly accurate diagnostic marker (AUC=1.000). Using novel in vitro models of MASH and CASH, we demonstrated that miR-210-5p modulation significantly affects lipid accumulation and cellular phenotype, with more pronounced effects in cholesterol-rich environments. Mechanistic studies revealed that miR-210-5p inhibition dramatically increased lipid accumulation and altered the expression of key metabolic regulators, suggesting its role as a metabolic mediator rather than the master regulator. These findings identify new molecular mechanisms in CASH pathogenesis, establish RETSAT as a potential diagnostic biomarker, and reveal promising therapeutic targets for intervention.